Metformin sensitizes sorafenib to inhibit postoperative recurrence and metastasis of hepatocellular carcinoma in orthotopic mouse models. Issue 1 (December 2016) - You, Abin; Cao, Manqing; Guo, Zhigui; Zuo, Bingfeng; Gao, Junrong; Zhou, Hongyuan; Li, Huikai; Cui, Yunlong; Fang, Feng; Zhang, Wei; Song, Tianqiang; Li, Qiang; et al.
Abstract Background Sorafenib is recognized as a standard treatment for advanced hepatocellular carcinoma (HCC). However, many patients have to adopt dose reduction or terminate the use of sorafenib because of side effects. In addition, a large number of patients are resistant to sorafenib. Thus, it is essential to investigate the underlying mechanisms of the resistance to sorafenib and seek potential strategy to enhance its efficacy. Methods The protein expression of hypoxia-inducible factors (HIF)-2α, 30-kDa HIV Tat-interacting protein (TIP30), E-cadherin, N-cadherin, and pAMPK was detected by Western blot. Cell viability assays were performed to study the influence of metformin and sorafenib on cell proliferation. Annexin V-FITC apoptosis assays were used to detect the influence of metformin and sorafenib on cell apoptosis. The relationship between HIF-2α and TIP30 was studied using gene silencing approach and chromatin immunoprecipitation assay. To investigate the effect of metformin and sorafenib on postoperative recurrence and lung metastasis of HCC in tumor-bearing mice, the mice were orally treated either with metformin or sorafenib once a day for continuous 37 days after the operation to remove the lobe where the tumor was implanted. CD31, Ki67, and TUNEL were examined by immunohistochemistry. Results Our study demonstrated that metformin synergized with sorafenib reduced HIF-2α expression as examined by Western blot. Gene silencing approach indicated TIP30 was upregulated after knocking-down of HIF-2α and chromatin immunoprecipitation assay revealed that HIF-2α could bind to TIP30 promoter under hypoxic condition. Cell Counting Kit-8 (CCK8) cell viability assay and Annexin V-FITC apoptosis assay showed that metformin in combination with sorafenib suppressed cell proliferation and promoted cell apoptosis. Besides, combined therapy suppressed epithelial-mesenchymal transition (EMT) process both in vitro and in vivo. Moreover, metformin in combination with sorafenib significantly minimized postoperative recurrence and lung metastasis of HCC in orthotopic mouse model. Combined therapy inhibited CD31 and Ki67 expression but promoted TUNEL expression. Conclusions Metformin may potentially enhance the effect of sorafenib to inhibit HCC recurrence and metastasis after liver resection by regulating the expression of HIF-2α and TIP30.